King Abdulaziz University students’ compliance with the values of digital citizenship in light of Islamic education directives - Alahmadi, Abdullah Attitallah (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal the reality of King Abdulaziz University students' compliance with the values of digital citizenship through its three axes: self-respect and respect for others, self-education and communication with others, self-protection and protection of others. The study used the descriptive approach, and information was collected from a questionnaire consisting of (24) paragraphs distributed on the axes of the values of digital citizenship, and the study sample consisted of (387) students from King Abdulaziz University in scientific and literary disciplines, Among the most prominent results: All the axes of the questionnaire obtained high averages with a very large degree of agreement in the compliance of King Abdulaziz University students with the values of digital citizenship, he ranking was as follows: the axis of self-respect and respect for others ranked first, with an arithmetic mean (4.07 out of 5), nd in the second place came the axis of self-education and communication with others, which got an arithmetic average of (4.05 out of 5), while the axis of self-protection and protection of others came in third place with an arithmetic average of (4.00 out of 5).
Keywords: values; digital citizenship values; Islamic education directives